Increasing foreign aid for inclusive human development in Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2017)
In the light of evidence that poverty has been decreasing in all regions of the World with the exception of Africa, where about 45 percent of countries in Sub-Saharan Africa did not achieve the Millennium Development Goal (MDG) extreme poverty target. Therefore, this study assesses whether increasing foreign aid improves inclusive human development. The investigation is on 53 African countries for the period 2005-2012. The empirical analysis is based on (i) the Generalised Method of Moments (GMM) to control for persistence in inclusive human development, simultaneity and time-invariant omitted variables and (ii) Instrumental Variable Tobit Regressions to control for simultaneity and the limited range in the dependent variable. The adopted foreign aid variables are: `humanitarian assistance', `action on debt' `aid for social infrastructure', `aid to the productive sector', `aid to the multi sector', `aid for economic infrastructure' and `programme assistance'. The following findings are established. From the GMM specifications, there are (i) synergy effects from `aid to the productive sector' and a positive net effect from `programme assistance' and (ii) negative net impacts from `aid to social infrastructure' and human assistance, albeit with positive marginal effects. From Instrumental Variable Tobit regressions (i) there is a synergy effect from `aid for economic infrastructure' and (ii) there are negative net impacts from `aid for social infrastructure', `aid to the productive sector' and human assistance, albeit with positive marginal effects. Policy implications are discussed.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Sustainable Development; Africa